Development of Interactive Game-Based Learning Media Assisted by Classpoint to Enhance Student Learning Motivation - Nur, Ilham Muhammad; Medriati, Rosane; Risdianto, Eko (Asian Journal of Science Education, 2024)
As a result of the needs analysis, students stated that they had difficulty understanding physics learning and needed encouragement for students to make it easier for them to understand learning. This study aims to determine the feasibility of developing media, know student responses to the development of media, and Know student motivation after using interactive game-based learning media assisted by the Classpoint application. This research uses the Research and Development (RD) method using the 4D model. The sample used was twenty-six students, and the teacher was one person. Research data were obtained through expert validation sheets, student response questionnaires, and student motivation pretest-posttest, which were analyzed qualitative and quantitative. The overall learning media validation results show a score of eighty-six point two, which is included in the very feasible category, student response is eighty-one percent, which shows a good category, and there is an increase in motivation of twelve point five percent which is classified as moderate motivation with N-Gain results of zero point four. as for the research subjects are tenth grade students of Public Senior High School 08 Bengkulu City.